2017
DOI: 10.5539/mas.v12n1p137
|View full text |Cite
|
Sign up to set email alerts
|

The Extent to Which Students Have Sufficient Awareness of E-Learning and its Relation to Self-Studying and Academic Achievement

Abstract: Rapid development of information and communication technologies poses education to improve the quality of the educational process. And today the main focus in the current learning process is shifting toward the model of e-learning, to which aim mainly to provide students with convenient and round-the-clock access to educational materials, this open access valuable and available e-learning models provides an improved modern learning model that improve the educational process. This study aims to investigate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…The questionnaire used in the current study consisted of eight sections: the first section measured the demographic data of the participants, and the other seven measured students’ satisfaction, system quality, three student factors, instructors’ performance quality, and course evaluation. Fifty-four items are shown in ( Table S1 ), and they were adopted from four previous studies [ 20 , 24 , 65 , 84 ]. All the constructed items were answered using a five-point Likert scale (5 = strongly agree, 4 = agree, 3 = uncertain, 2 = disagree, and 1 = strongly disagree).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The questionnaire used in the current study consisted of eight sections: the first section measured the demographic data of the participants, and the other seven measured students’ satisfaction, system quality, three student factors, instructors’ performance quality, and course evaluation. Fifty-four items are shown in ( Table S1 ), and they were adopted from four previous studies [ 20 , 24 , 65 , 84 ]. All the constructed items were answered using a five-point Likert scale (5 = strongly agree, 4 = agree, 3 = uncertain, 2 = disagree, and 1 = strongly disagree).…”
Section: Methodsmentioning
confidence: 99%
“…All the constructed items were answered using a five-point Likert scale (5 = strongly agree, 4 = agree, 3 = uncertain, 2 = disagree, and 1 = strongly disagree). The internal consistency of these constructs was satisfactory as reported in the previous studies: student–instructor interaction (five items; alpha = 0.737; [ 84 ]), instructor performance quality (four items; alpha = 0.882; [ 84 ]), course evaluation (six items; alpha = 0.882; [ 84 ], social presence (12 items; alpha = 0.94; [ 65 ]), system quality (four items; alpha = 0.680; [ 20 ]), students’ awareness toward using e-learning in the educational process (16 items; alpha = 0.70; [ 24 ]), and students’ satisfaction (seven items; alpha = 0.89; [ 65 ]). In addition to the previous studies which developed and evaluated these instruments [ 85 , 86 , 87 , 88 , 89 ], the current study used advanced analyses to evaluate the psychometric properties of these instruments for each respective factor.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the items of each construct and their corresponding loading are presented in appendix A. [23], [25] Q13 University Ability (UA) 3/5 [22], [26], [27] Q14 Data Governance (DG) 5/6 [22], [24], [29], [28], [30] Q15 Technological Infrastructure (TI) 3/3 [22], [31] Q16 Learning Analytics Awareness (LAW) 5/5 [24], [28], [36], [37] Q17 Learning Analytics impact (LAI) 7/8 [24], [39]…”
Section: Methodsmentioning
confidence: 99%
“…It refers to the level of understanding of learning analytics among stakeholders and the realization of the advantages and usage of learning analytics [28], [24]. Although raising awareness is vital for increasing technology adoption, it is sometimes overlooked as a component in adoption [36], [37]. It is suggested that individuals with high technology awareness may perceive technological impact positively [38].…”
Section: ─ Learning Analytics Awareness (Law) and Learning Analytics ...mentioning
confidence: 99%